Identifying Supply Chain Performance of Organic Rice in Lampung - Sri Handayani; Muhammad Irfan Affandi; Luluk Irawati (International Journal of Applied Business and International Management, 2019)
Lampung Province has organic rice fields which always increase with a planting area of 65.78 hectares. The problem of farmers is the limited access to the organic rice market. Products can’t be sold at organic prices; some are still sold by farmers at non-organic prices. Organic rice supply chain networks need to be identified by farmers so that farmers have market information and supply chain performance. For this reason, this research purpose to analyze the supply chain of organic rice in Pringsewu Regency. Data analysis method uses the concept of supply chain performance with the Supply Chain Operations Reference (SCOR) approach. SCOR consists of five elements including flexibility, reliability, responsiveness, assets, and cost. The results of performance organic rice supply chains at all levels in the attributes of flexibility and responsiveness have achieved the superior performance position. The performance of organic rice supply chains attributes of asset at the farm level only achieves an advantage. But the supply chain performance in the attribute of reliability has not been able to reach a good performance position. So, there needs to be an improvement effort through disciplinary shipping arrangements and product quality improvements to improve supply chain performance.